2009
DOI: 10.1021/jo9007095
|View full text |Cite
|
Sign up to set email alerts
|

Radical-Scavenging Activity and Mechanism of Resveratrol-Oriented Analogues: Influence of the Solvent, Radical, and Substitution

Abstract: Resveratrol (3,5,4'-trihydroxy-trans-stilbene, 3,5,4'-THS) is a well-known natural antioxidant and cancer chemopreventive agent that has attracted much interest in the past decade. To find a more active antioxidant and investigate the antioxidative mechanism with resveratrol as the lead compound, we synthesized 3,5-dihydroxy-trans-stilbene (3,5-DHS), 4-hydroxy-trans-stilbene (4-HS) 3,4-dihydroxy-trans-stilbene (3,4-DHS), 4,4'-dihydroxy-trans-stilbene (4,4'-DHS), 4-hydroxy-3-methoxy-trans-stilbene (3-MeO-4-HS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
103
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(115 citation statements)
references
References 45 publications
11
103
0
1
Order By: Relevance
“…This modification can be explained based on the fact that a proton is first lost by an acid-base equilibrium to give the phenoxide anion followed by a very fast electron transfer from these species to radical (SPLET). According to their approach, we also confirm by studying the effect of added acetic acid on the measured rate constant that the radical-scavenging reaction of resveratrol analogues in ethanol primarily involved the SPLET mechanism (Shang et al 2009). Hydroxycinnamic acid derivatives, which are relatively strong acids, are in equilibrium with the carboxylic anion and H + in methanol that supports ionisation.…”
Section: Gosupporting
confidence: 54%
See 1 more Smart Citation
“…This modification can be explained based on the fact that a proton is first lost by an acid-base equilibrium to give the phenoxide anion followed by a very fast electron transfer from these species to radical (SPLET). According to their approach, we also confirm by studying the effect of added acetic acid on the measured rate constant that the radical-scavenging reaction of resveratrol analogues in ethanol primarily involved the SPLET mechanism (Shang et al 2009). Hydroxycinnamic acid derivatives, which are relatively strong acids, are in equilibrium with the carboxylic anion and H + in methanol that supports ionisation.…”
Section: Gosupporting
confidence: 54%
“…Sensors l scavenging activity and antioxidant mechanism of chalcones and resveratrol analogues by studying the influences of solvents, radicals, and substitutions on the antioxidant activity (Shang et al 2009;Qian et al 2011). Hydroxycinnamic acids are organic acids, with pK a values ranging from 4 to 5 (Beltrán et al 2003).…”
Section: Food Chemistry and Safetymentioning
confidence: 99%
“…[4a, 6] Recently, we found that introduction of electron-donating substituents in the ortho-or para-position of the 4'-OH could significantly enhance its antioxidant activity, [7] prooxidant activity on DNA damage in the presence of Cu II ions, [8] and cytotoxicity on human promeolocytic leukemia cells. [9] The hybrid approach has recently attracted much attention in medicinal chemistry and design of hybrid molecules encompassing two pharmacophores in one molecular scaffold is a niche area in a large field of drug discovery.…”
mentioning
confidence: 99%
“…Resveratrol is believed to have the various biological abilities such as antioxidant and anti-inflammatory effects (4). Previous experiments have shown that resveratrol is able to scavenge free radicals directly by hydrogen atom transfer and sequential proton loss electron transfer (5,6). Resveratrol has the anti-tumor effect against various cancer types due to inhibition of cell proliferation, induce apoptosis and suppress metastasis and invasion in a number of cell lines.…”
Section: Introductionmentioning
confidence: 99%